Discovery of a 0.42-s pulsar in the ultraluminous X-ray source NGC 7793 P13. (26th October 2016) - Israel, G. L.; Papitto, A.; Esposito, P.; Stella, L.; Zampieri, L.; Belfiore, A.; Rodríguez Castillo, G. A.; De Luca, A.; Tiengo, A.; Haberl, F.; Greiner, J.; Salvaterra, R.; et al.
Abstract: NGC 7793 P13 is a variable (luminosity range ∼100) ultraluminous X-ray source proposed to host a stellar-mass black hole of less than 15 M⊙ in a binary system with orbital period of 64 d and a 18–23 M⊙ B9Ia companion. Within the EXTraS (Exploring the X-ray Transient and variable Sky) project, we discovered pulsations at a period of ∼0.42 s in two XMM–Newton observations of NGC 7793 P13, during which the source was detected at L X ∼ 2.1 × 10 39 and 5 × 10 39 erg s −1 (0.3–10 keV band). These findings unambiguously demonstrate that the compact object in NGC 7793 P13 is a neutron star accreting at super-Eddington rates. While standard accretion models face difficulties accounting for the pulsar X-ray luminosity, the presence of a multipolar magnetic field with B ∼ few × 10 13  G close to the base of the accretion column appears to be in agreement with the properties of the system.